2011
DOI: 10.3390/rs3020362
|View full text |Cite
|
Sign up to set email alerts
|

Field Spectroscopy for Assisting Water Quality Monitoring and Assessment in Water Treatment Reservoirs Using Atmospheric Corrected Satellite Remotely Sensed Imagery

Abstract: Abstract:The overall objective of this study was to use field spectro-radiometers for finding possible spectral regions in which chlorophyll-a (Chl-a) and particulate organic carbon (POC) could be identified so as to assist the assessment and monitoring of water quality using satellite remote sensing technology. This paper presents the methodology adopted in this study which is based on the application of linear regression analysis between the mean reflectance values (measured with the GER1500 field spectro-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…The dark-object subtraction (DOS), a histogram minimum method proposed by Chavez [29], was compared with the Quick Atmospheric Correction (QUAC) that is a VNIR-SWIR atmospheric correction method [30] in this study. The DOS was demonstrated as the most effective method for monitoring water quality using visible bands [31,32], while QUAC showed accurate performance for infrared spectral bands [30]. Ha and Koike [33] also identified that DOS was a more suitable atmospheric correction method for the MODIS image data of Tien Yen Bay than the near-infrared atmospheric correction and Fast Line-of-sight Atmospheric Analysis of Hyperspectral cubes (FLAASH).…”
Section: Modis Image Datamentioning
confidence: 99%
“…The dark-object subtraction (DOS), a histogram minimum method proposed by Chavez [29], was compared with the Quick Atmospheric Correction (QUAC) that is a VNIR-SWIR atmospheric correction method [30] in this study. The DOS was demonstrated as the most effective method for monitoring water quality using visible bands [31,32], while QUAC showed accurate performance for infrared spectral bands [30]. Ha and Koike [33] also identified that DOS was a more suitable atmospheric correction method for the MODIS image data of Tien Yen Bay than the near-infrared atmospheric correction and Fast Line-of-sight Atmospheric Analysis of Hyperspectral cubes (FLAASH).…”
Section: Modis Image Datamentioning
confidence: 99%
“…Remote sensing techniques have been extensively used for monitoring chl-a in aquatic systems [4,[8][9][10]. The advantages of using remote sensing techniques to monitor chl-a are: (1) the geographical coverage of satellite images, which provide information about the entire aquatic system; (2) remote sensing, which allows us to obtain information from inaccessible places; and (3) historical satellite images, which allow the inference of water quality information from the past records [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for estimating chl-a concentration in different turbid waters (Case 2) with remote sensing have been investigated [4][5][6][7][8][9][10][11][12]. Many studies have suggested that remote spectroscopic measurements from the Moderate Resolution Imaging Spectroradiometer (MODIS) should be used to estimate chl-a concentrations in Case 2 waters through empirical and semi-empirical algorithms [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The POC/Chl-a is in the range of fresh phytoplankton ranges, between 33 and 100 [66]; this is much higher than that of sub-Antarctic water (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) [67], Great Wall Cove and Ardley Cove (74.62 ± 27.97) [65] and the East China Sea (64) [68]. However, it is much lower than that of dystrophic water (250-2500) [69], the Pacific Ocean (178 ± 30) [70], the Atlantic Ocean (253) and other ocean subsystems ( Table 2 in Fabiano et al [71]; Arrigo et al [72]; Table1 in Hadjimitsis et al [73]). The effect of atmospheric correction on the POC algorithm also should be considered in addition to the dominant water constituents of POC.…”
Section: Probable Source Of Pocmentioning
confidence: 99%